Effect of Gas Flow Rate on Spectral Properties of Magnetically Stabilized Gliding Arc Discharge Plasma - Abdullah, Nada A.; Kadhem, Saba J. (Iraqi Journal of Science, 2024)
In this paper, the Magnetically Stabilized Gliding Arc Discharge (MSGAD) system was constructed to produce non-thermal plasma using argon gas under atmospheric pressure. A gliding plasma discharge was stabilized by a magnetic field for the purpose of a planned investigation. The emission spectra of the generated plasma using a gliding arc discharge system were recorded under atmospheric pressure, with a constant value of alternating voltage (4 kV) and at different gas flow rates of) 0.5–2.5 (L/min. The plasma parameters, including electron temperature (Te), electron density (ne), plasma frequency, Debye length and electron temperature, were calculated. The electron temperature was measured using the Boltzmann plot method, and the electron density was determined using the Stark broadening method. The results show an increase of the electron temperature from 1.138 to 1.277eV and electron density from 2.78×1017 to 3.48×1017 cm-3 as the gas flow increased from 0.5 to 2.5 L/min. Also, the spectral line intensity increases with the increase of the gas flow rate.